Political and Legal Aspects of The Israeli and Palestinian Conflict - Atep Abdurofiq; Gilang Rizki Aji Putra (Jurnal Cita Hukum, 2023)
The Israeli-Palestinian conflict has a long history spanning several decades and encompasses intricate political and legal dimensions. This battle not only had repercussions for both parties involved but also garnered international scrutiny and emerged as a significant matter in global diplomacy. This article seeks to examine the political and legal dimensions of the conflict, namely Israel's diplomatic acts that contravene international legal standards, as well as the suggested and implemented attempts for resolving the conflict. This study employs qualitative research methodologies with a focus on reviewing existing literature. The literature review includes the examination of international legal documents, UN resolutions, and peace accords, as well as articles and books that analyze the Israeli-Palestinian issue from a political and legal standpoint. The collected data is evaluated to discern patterns of lawlessness exhibited by Israel and assess the efficacy of different conflict resolution strategies. The research findings indicate that Israeli diplomatic acts frequently contravene the tenets of international law, such as engaging in unlawful occupation and establishing colonies in Palestinian lands. Despite the implementation of multiple resolutions and diplomatic initiatives aimed at resolving the issue, the outcomes have been restricted and frequently hindered by political motivations and a mutual unwillingness to make concessions. To establish durable peace, it is necessary to adopt a more comprehensive approach and include the international community in addressing the Israeli-Palestinian problem.